2018
DOI: 10.1093/humupd/dmy002
|View full text |Cite
|
Sign up to set email alerts
|

The importance of DNA repair for maintaining oocyte quality in response to anti-cancer treatments, environmental toxins and maternal ageing

Abstract: Primordial follicle oocytes are vulnerable to DNA DSBs emanating from endogenous and exogenous sources. The ability to repair this damage is essential for female fertility. In the long term, augmenting DNA repair in primordial follicle oocytes has implications for the development of novel fertility preservation agents for female cancer patients and for the management of maternal ageing. However, further work is required to fully characterize the specific proteins involved and to develop strategies to bolster t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
110
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(118 citation statements)
references
References 158 publications
3
110
0
1
Order By: Relevance
“…In the present study, we identified two novel heterozygous frameshift mutations of the FANCL gene in POI patients, p.Gln350Valfs*18 and p.Met247Asnfs*4, that resulted in the loss of ubiquitin‐ligase activity and impaired DNA damage repair capacity. It is well documented that the maintenance of genome stability and integrity is a vital determinant of cell viability, and the germ cell genome is especially vulnerable to ubiquitous DNA insults (Winship, Stringer, Liew, & Hutt, 2018). Moreover, increasing evidence suggests that mutations of the genes involved in DNA repair underlie the pathogenesis of POI (Huhtaniemi et al, 2018; Jiao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we identified two novel heterozygous frameshift mutations of the FANCL gene in POI patients, p.Gln350Valfs*18 and p.Met247Asnfs*4, that resulted in the loss of ubiquitin‐ligase activity and impaired DNA damage repair capacity. It is well documented that the maintenance of genome stability and integrity is a vital determinant of cell viability, and the germ cell genome is especially vulnerable to ubiquitous DNA insults (Winship, Stringer, Liew, & Hutt, 2018). Moreover, increasing evidence suggests that mutations of the genes involved in DNA repair underlie the pathogenesis of POI (Huhtaniemi et al, 2018; Jiao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…DNA breaks are more likely to remain unrepaired in aged oocytes owing to reduced expression of DNA repair genes such as ATM, BRCA1, and RAD51 (Titus et al, 2013;Winship et al, 2018). Consistent with this, oocytes from mice with reduced BRCA1 expression or disrupted RAD51 function exhibit increased DNA damage (Kujjo et al, 2010;Titus et al, 2013;Winship et al, 2018). Thus, low levels of DNA damage may persist throughout oocyte growth without inducing apoptosis, especially when DNA repair capacity is compromised.…”
Section: Introductionmentioning
confidence: 81%
“…In contrast, full activation of TAp63 at high irradiation doses (0.45 Gy) causes virtually all oocytes to succumb (Suh et al, 2006). DNA breaks are more likely to remain unrepaired in aged oocytes owing to reduced expression of DNA repair genes such as ATM, BRCA1, and RAD51 (Titus et al, 2013;Winship et al, 2018). Consistent with this, oocytes from mice with reduced BRCA1 expression or disrupted RAD51 function exhibit increased DNA damage (Kujjo et al, 2010;Titus et al, 2013;Winship et al, 2018).…”
Section: Introductionmentioning
confidence: 87%
“…Many working in oncofertility research are now turning their attention to the development of drugs that can prevent initial oocyte damage, thus preserving the ovarian follicle pool as well as ovarian endocrine function. Recent evidence suggests that cancer therapies reduce the primordial follicle pool by promoting DNA damage and apoptosis in their oocytes (Winship et al 2018). The proapoptotic protein p53 upregulated modulator of apoptosis (PUMA) was identified as critical apoptotic trigger in ovarian reserve depletion following chemotherapy.…”
Section: Speakers: Iain Clarke Ray Rodgers Graeme Martin Karla Huttmentioning
confidence: 99%